At the Mercy of Strategies: The Role of Motor Representations in Language Understanding - Tomasino, Barbara; Rumiati, Raffaella I. (Frontiers in Psychology, 2013)
Classical cognitive theories hold that word representations in the brain are abstract and amodal, and are independent of the objects’ sensorimotor properties they refer to. An alternative hypothesis emphasises the importance of bodily processes in cognition: the representation of a concept appears to be crucially dependent upon perceptual-motor processes that relate to it. Thus, understanding action-related words would rely upon the same motor structures that also support the execution of the same actions. In this context, motor simulation represents a key component. Our approach is to draw parallels between the literature on mental rotation and the literature on action verb/sentence processing. Here we will discuss recent studies on mental imagery, mental rotation, and language that clearly demonstrate how motor simulation is neither automatic nor necessary to language understanding. These studies have shown that motor representations can or cannot be activated depending on the type of strategy the participants adopt to perform tasks involving motor phrases. On the one hand, participants may imagine the movement with the body parts used to carry out the actions described by the verbs (i.e., motor strategy); on the other, individuals may solve the task without simulating the corresponding movements (i.e., visual strategy). While it is not surprising that the motor strategy is at work when participants process action-related verbs, it is however striking that sensorimotor activation has been reported also for imageable concrete words with no motor content, for “non-words” with regular phonology, for pseudo-verb stimuli, and also for negations. Based on the extant literature, we will argue that implicit motor imagery is not uniquely used when a body-related stimulus is encountered, and that it is not the type of stimulus that automatically triggers the motor simulation but the type of strategy. Finally, we will also comment on the view that sensorimotor activations ar